2019
DOI: 10.1016/j.ajog.2019.02.058
|View full text |Cite
|
Sign up to set email alerts
|

M281, an anti-FcRn antibody, inhibits IgG transfer in a human ex vivo placental perfusion model

Abstract: BACKGROUND:The transfer of pathogenic immunoglobulin G antibodies from mother to fetus is a critical step in the pathophysiology of alloimmune and autoimmune diseases of the fetus and neonate. Immunoglobulin G transfer across the human placenta to the fetus is mediated by the neonatal Fc receptor, and blockade of the neonatal Fc receptor may provide a therapeutic strategy to prevent or minimize pathological events associated with immune-mediated diseases of pregnancy. M281 is a fully human, aglycosylated monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
(23 reference statements)
0
39
0
3
Order By: Relevance
“…Nipocalimab binds with picomolar affinity to FcRn at both endosomal pH 6.0 and extracellular pH 7.6 allowing occupancy of FcRn throughout the recycling pathway and has a specificity designed to minimize off target effects (22). It is not expected to cross the placenta and a clinical trial is underway in pregnant women at high risk for early onset severe hemolytic disease of the fetus and newborn (23,24). Phase 1 data supports infusion rates of 7.5 or 15 min for 30 and 60 mg/kg doses, respectively (25).…”
Section: Nipocalimabmentioning
confidence: 99%
“…Nipocalimab binds with picomolar affinity to FcRn at both endosomal pH 6.0 and extracellular pH 7.6 allowing occupancy of FcRn throughout the recycling pathway and has a specificity designed to minimize off target effects (22). It is not expected to cross the placenta and a clinical trial is underway in pregnant women at high risk for early onset severe hemolytic disease of the fetus and newborn (23,24). Phase 1 data supports infusion rates of 7.5 or 15 min for 30 and 60 mg/kg doses, respectively (25).…”
Section: Nipocalimabmentioning
confidence: 99%
“…Two other FcRn-directed antibodies have completed phase II testing for MG without published results but appear to be moving to phase III investigation. Nipocalimab is a human monoclonal antibody high-affinity binding to the FcRn in the picomolar range [65]. A phase II study in MG has been completed with positive results reported by the company (NCT03772587) [66].…”
Section: Neonatal Fc Receptor Inhibitionmentioning
confidence: 99%
“…M281 is a monoclonal antibody which binds to the neonatal Fc receptor to inhibit transplacental IgG transfer (Figure A and Figure B) . Early phase trials with M281 in healthy nonpregnant volunteers have shown that circulating IgG levels are reduced on average by 84%, perhaps by inhibiting the recycling of IgG in vascular endothelial cells which contributes to their usually long half‐life . Animal experiments prior to the phase 1 study yielded encouraging toxicology and efficacy data .…”
Section: The Potential Use Of Monoclonal Antibody M281 (Nipocalimab)mentioning
confidence: 99%
“…Early phase trials with M281 in healthy nonpregnant volunteers have shown that circulating IgG levels are reduced on average by 84%, perhaps by inhibiting the recycling of IgG in vascular endothelial cells which contributes to their usually long half‐life . Animal experiments prior to the phase 1 study yielded encouraging toxicology and efficacy data . If passage of pathogenic maternal IgG to a fetus can be blocked then immune‐mediated conditions could be prevented.…”
Section: The Potential Use Of Monoclonal Antibody M281 (Nipocalimab)mentioning
confidence: 99%
See 1 more Smart Citation